Emotional Intelligence Review Based on Differences of Parenting Style in High School Students - Girsang, Evi Safitri; Nainggolan, Susi Meliati; Manurung, Yulinda Septiani (Universitas Muhammadiyah Metro, 2019)
Emotional intelligence individuals include self-control, resilience, enthusiasm, and abilities to encourage oneself, resilience, and control impulses and emotions. Emotional intelligence has a vital role in one's success, beyond rational or intellectual intelligence. The parenting style of the parents influences the emotional intelligence of a child. One of the factors that influence children's emotional development is the discipline applied by parents. The research objective was to determine the correlation between parenting style with students' emotional intelligence in class XI SMA Santo Thomas 2 Medan. This study uses a quantitative approach with the type of ex post facto research. The population in this study were students of class XI SMA Santo Thomas 2 Medan with a total o,f 307 students. The data collection technique uses a scale to collect parenting style data for parents and emotional intelligence. The validity test uses expert judgment, and the reliability test uses Alpha Cronbach the technique. The data analysis technique used regression analysis. The results showed that the correlation between parenting style and emotional intelligence was 53.3%. The results of the regression analytic show (1) there is no correlation between authoritarian parenting style and students' emotional intelligence, with a value of r = 0.029 and a significance of p = 0.260. (2) there is no correlation between the authoritative parenting style and students' emotional intelligence, with a value of r = 0.736 and a significance of p = 0.720. (3) there is a negative correlation between parenting style rejecting with students' emotional intelligence, with a value of r = 0.010 and a significance of p = -0.008.